2013
DOI: 10.1371/journal.pone.0052559
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cycle Gene Expression in Aedes aegypti Brains by In Situ Hybridization

Abstract: Even though the blood-sucking mosquito Aedes aegypti is one of the most important disease vectors, relatively little is known about the molecular mechanisms underlying processes involved in the temporal pattern of its activity and host seeking behavior. In this study, we analyzed the expression of the cycle (cyc) gene, one of the core components of the circadian clock, in Ae. aegypti brains by in situ hybridization at two different time points in light-dark conditions and compared the results with those obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
0
9
0
1
Order By: Relevance
“…Previous research has indicated that the major risk areas for dengue are: urban areas, areas with high population density, areas with informal settlements and in places where sanitation conditions are not satisfactory. In those areas, the female mosquito finds conditions in which it can feed and reproduce [29, 30]. Further, the Brazilian coast is densely populated since the major Brazilian urban centers are located on the coast or near it (e.g., São Paulo, Rio de Janeiro and Salvador).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that the major risk areas for dengue are: urban areas, areas with high population density, areas with informal settlements and in places where sanitation conditions are not satisfactory. In those areas, the female mosquito finds conditions in which it can feed and reproduce [29, 30]. Further, the Brazilian coast is densely populated since the major Brazilian urban centers are located on the coast or near it (e.g., São Paulo, Rio de Janeiro and Salvador).…”
Section: Discussionmentioning
confidence: 99%
“…Some arboviruses are able to invade several tissues including the mosquito’s brain and are likely to modify its physiology and metabolism. Hence, arboviruses are prone to affect vectorial capacity and the pattern of disease transmission [ 17 , 18 ]. A reoccurring observation noted in several studies is the effect of senescence and pathogen infection on fecundity ( i .…”
Section: Introductionmentioning
confidence: 99%
“…aegypti timeless gene ( tim, AAEL006411) [28]; brain in situ hybridization of Ae. aegypti cycle ( cyc , AAEL002049) [29]; the expression profiling of clock genes in Ae. aegypti, An.…”
Section: Introductionmentioning
confidence: 99%